General description of the habitat of Acropora halmahera based on a literature approach (Wallace & Wolstenhome 1998) - Firdaut Ismail; Abdul Ajiz Siolimbona; Nebuchadnezzar Akbar; Rustam E Paembonan; Irmalita Tahir; Najamuddin Najamadidin; Abdul Motalib Angkotasan (Depik, 2025)
Acropora halmahera is one of the coral species that has an important role in the coral reef ecosystem Wolstenhome (1998) found in Loloda Island. A. halmahera is an endemic species found in the Halmahera sea. This coral species has not yet received information about the distribution in the marine area of the North Maluku archipelago. Habitat influences morphogenetics. Information on the general description of the habitat of this species has not been found (unpublished). A. halmahera is a coral species that ecologically also plays a role in influencing sedimentation rates and serves as a place for marine organisms to live. The study aims to describe the habitat of A. halmahera in Small Islands, North Maluku. Data collection of Acropora halmahera and coral life forms on three islands using Line Intercep Transect (LIT). Samples of A. halmahera were taken 32 cm branch. Morphometric measurements of A. halmahera were conducted in the laboratory. Environmental variables were takenwas conducted to see the relationship of the environment to the station. The results showed that A. halmahera has a habitat preference at a depth of 5-20 meters, temperature 29-33 C, salinity 32-35 ppt, and pH 7.1-8. Sandy bottom substrate conditions for the growing area of A. halmahera species. PCA analysis showed that each station characterized environmental variables. Data showed that 13 coral life forms were found with variations in coral cover at each station. The environment was generally favorable for species to grow and thrive. These findings provide useful insights for coral reef conservation and management in the Halmahera region, and can serve as a reference for further research on other coral species.Keywords:EndemicArchipelagoBranching CoralMorphologySmall Island